Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1073/pnas.1222729110
|View full text |Cite
|
Sign up to set email alerts
|

CFTR-deficient pigs display peripheral nervous system defects at birth

Abstract: Peripheral nervous system abnormalities, including neuropathy, have been reported in people with cystic fibrosis. These abnormalities have largely been attributed to secondary manifestations of the disease. We tested the hypothesis that disruption of the cystic fibrosis transmembrane conductance regulator (CFTR) gene directly influences nervous system function by studying newborn CFTR −/− pigs. We discovered CFTR expression and activity in Schwann cells, and loss of CFTR caused ultrastructural myelin sheath ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 59 publications
1
40
0
Order By: Relevance
“…Interestingly, in humans with CF, the number of pulmonary neuroendocrine cells is elevated. 73,74 Our studies in the pig suggest that innervation of the sinuses 55 and trachea 75 is also decreased. …”
Section: Innervationmentioning
confidence: 72%
See 1 more Smart Citation
“…Interestingly, in humans with CF, the number of pulmonary neuroendocrine cells is elevated. 73,74 Our studies in the pig suggest that innervation of the sinuses 55 and trachea 75 is also decreased. …”
Section: Innervationmentioning
confidence: 72%
“…37 In pigs, CFTR is expressed in both the peripheral and central nervous systems. 55,56 In humans, CFTR has been identified in parvocellular ganglion, 57 hypothalamic neurons, 58 spinal cord neurons, 59 ganglion cells of the heart, 60 and sympathetic ganglion. 61 Both neuronal and glial cell CFTR expression has been reported in multiple species, 55,[62][63][64] with the exception of humans, in whom only neuronal CFTR has been reported.…”
Section: Cftr Expression and Function In The Nervous Systemmentioning
confidence: 99%
“…Pulmonary innervation begins very early in gestation (47) and baseline airway caliber is in part regulated by neural control (49). Innervation abnormalities have been reported in the airways of a CF mouse model (50), and we recently reported that pigs with CF have nervous system abnormalities at birth (51). Might altered nervous system function and/or innervation contribute to the airway phenotype?…”
Section: Airway Size Reduction and Potential Mechanismsmentioning
confidence: 99%
“…In autopsy reports of adults with CF, axonal dystrophy has been described in 75% of the brains as well as in the few examined spinal cords (Cavalier and Gambetti 1981;Cochran et al 1991). Even if these symptoms may result from a complex association of diabetes, autoimmunity and vitamin deficiency, a primary CFTR defect is also likely to be involved as shown by the recent report of peripheral nervous system defects observed in CFTR -/-pigs at birth (Reznikov et al 2013). Concerning CFTR protein function, recent works have studied CFTR activity in motor neurons of the spinal cord or brainstem nuclei in rats during neonatal development (Ostroumov et al 2007;Morales et al 2011) and have shown that CFTR contributes to the relatively depolarized equilibrium potential for synaptic inhibition, an important process to control hyperexcitability and seizure-predisposition in neonates (Ostroumov et al 2007).…”
Section: Discussionmentioning
confidence: 99%